2008
DOI: 10.1007/s10461-008-9483-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV/AIDS Behavioral Interventions in China: A Literature Review and Recommendation for Future Research

Abstract: In the past two decades, China has witnessed an alarming increase of HIV/AIDS epidemic. Meanwhile, a number of HIV prevention interventions have been conducted. This study reviews existing studies in literature on behavioral interventions on HIV/AIDS in China. Of 25 studies we identified, most have been concentrated in South and South–West China, mainly targeting injection drug users and female sex workers. The most commonly used intervention strategy was individual-oriented HIV-related knowledge education and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
71
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 37 publications
(108 reference statements)
2
71
0
Order By: Relevance
“…A systematic review of HIV prevention programs in China identified a growing body of individual-level behavioral interventions delivered in clinical settings and high-risk venues, and noted an emerging interest in workplace interventions (Hong and Li, 2009). Differences in HIV risk according to workplace settings call for the development of tailored workplace interventions.…”
Section: Implications For Health Promotion and Practitionersmentioning
confidence: 99%
“…A systematic review of HIV prevention programs in China identified a growing body of individual-level behavioral interventions delivered in clinical settings and high-risk venues, and noted an emerging interest in workplace interventions (Hong and Li, 2009). Differences in HIV risk according to workplace settings call for the development of tailored workplace interventions.…”
Section: Implications For Health Promotion and Practitionersmentioning
confidence: 99%
“…This study represents a marked departure from earlier FSW interventions in China by virtue of its higher recruitment rate, improved retention, measurement of syphilis and HIV incidence, and oversampling of FSWs from low-tier sex venues [3,[18][19][20]. One study reported approaching 13 785 FSWs but enrolling only 977 (7.1%), [18] making our enrollment rate of 49.3% (3597 of 7297) a substantial improvement.…”
Section: Discussionmentioning
confidence: 94%
“…First, whereas most traditional FSW interventions have focused on condom use and increasing individual HIV knowledge, [20] this community structural intervention focused on creating mutual trust and sustainable connections between sex venues and STI clinics. Especially in local contexts where private clinics may not have standardized STI services or licensed doctors, [22] re-establishing trust and relationships with local standardized STI clinics may have been a powerful force in preventing syphilis.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the HIV prevention interventions in China focus on improving HIV knowledge, awareness of HIV, attitudes towards condom use, and condom use (Hong & Li, 2009), few emphasize improving the assertiveness and the frequency of communication about condom use among target audience (Zhang, Li, Shah, Baldwin, & Stanton, 2007). It is important to understand the characterisitcs of assertive sexual communication of Chinese migrants so that variations in safer sex negotiation skills can be discovered.…”
Section: Discussionmentioning
confidence: 99%